2009
DOI: 10.1021/jp9000434
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Binding of Na+ versus K+ to the Carboxylic Acid Headgroup of Palmitic Acid Monolayers Studied by Vibrational Sum Frequency Generation Spectroscopy

Abstract: Ionic binding of alkali ions Na(+) and K(+) to the carboxylic acid headgroups of fatty acid monolayers is studied as a proxy toward understanding the fundamental chemistry in cell biology. In this study, we used broad-bandwidth sum frequency generation (BBSFG) vibrational spectroscopy to investigate the ionic binding event that leads to deprotonation and complex formation of fatty acid headgroups. Palmitic acid (C(15)H(31)COOH) exists as a monolayer on aqueous surfaces. Surface vibrational stretch modes of pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
189
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(209 citation statements)
references
References 38 publications
20
189
0
Order By: Relevance
“…A third peak appears in the spectrum of 1 near 1,440 cm −1 . Similar carboxylate peak frequencies have been observed in VSF spectroscopic studies of carboxylate-metal ion complexes, which were attributed to the disruption of carboxylate solvation shells due to the closeness of the cations (32,33). FTIR studies of simple carboxylic acids have additionally shown that the frequency of the peak attributed to the COO − antisymmetric stretch of a carboxylate-amine complex (34) is blue-shifted by ∼40 cm −1 relative to that of a fully water-solvated carboxylate group (35).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…A third peak appears in the spectrum of 1 near 1,440 cm −1 . Similar carboxylate peak frequencies have been observed in VSF spectroscopic studies of carboxylate-metal ion complexes, which were attributed to the disruption of carboxylate solvation shells due to the closeness of the cations (32,33). FTIR studies of simple carboxylic acids have additionally shown that the frequency of the peak attributed to the COO − antisymmetric stretch of a carboxylate-amine complex (34) is blue-shifted by ∼40 cm −1 relative to that of a fully water-solvated carboxylate group (35).…”
Section: Resultssupporting
confidence: 73%
“…Interfacial tension measurements were obtained at the oil-water interface using the Wilhelmy plate method according to a previously described procedure (32). Briefly, a platinum plate attached to a balance (KSV) was lowered to the neat CCl 4 -H 2 O interface and the interfacial tension was measured to be 44-46 mN/m.…”
Section: Methodsmentioning
confidence: 99%
“…For a typical fatty acid monolayer, however, as a result of the different protonation state of the carboxy group, more pronounced variations of the OH network feature have been reported. Qualitatively, a broad peak centered at 3560-3620 cm −1 becomes prominent, which has been attributed to weakly interacting OH groups between fatty acid and water molecules [Miranda et al, 1998;Johnson et al, 2005;Tang and Allen, 2009]. For seawater with pH values around 8, the carboxy group of short-chain fatty acids with pK a values around 4.8 is largely deprotonated, whereas long-chain fatty acids with pK a > 8.5 can be assumed to be largely protonated [Kanicky and Shah, 2002].…”
Section: Surfactant Effectsmentioning
confidence: 99%
“…Several studies have shown that the replacement of a pure water subphase with inorganic salt solutions causes alterations in the phase behavior of the monolayer, especially for FAs and phospholipids [31][32][33][34][35][36][37]. The effect of Ca 2+ has been widely investigated due to its relevance in biological membranes [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%